2021
DOI: 10.1177/10760296211057903
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-27b as a Biomarker of the Development and Progression of Carotid Artery Stenosis

Abstract: Objective A close relationship of microRNAs (miRNAs) with various human diseases has been widely reported, including cardiovascular disease. The current study attempted to examine the abnormal expression of miR-27b in asymptomatic carotid artery stenosis (ACAS), its diagnostic value and predictive value for the development of ACAS were also assessed. Methods Clinical serum samples were collected from both ACAS patients and healthy individuals, and levels of miR-27b in the clinical samples were detected using R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…In agreement with this study, He et al [ 52 ] concluded that lower plasma levels of miRNA-29b may be used as independent risk factors for the incidence of cardiovascular events (CVEs) and CAC. Lu et al [ 54 ] focused their study on the role of miR-27b: high levels of this miRNA may predict the occurrence of asymptomatic carotid artery stenosis (ACAS), with a high risk of generating subsequent cerebral ischemia events (CIEs).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this study, He et al [ 52 ] concluded that lower plasma levels of miRNA-29b may be used as independent risk factors for the incidence of cardiovascular events (CVEs) and CAC. Lu et al [ 54 ] focused their study on the role of miR-27b: high levels of this miRNA may predict the occurrence of asymptomatic carotid artery stenosis (ACAS), with a high risk of generating subsequent cerebral ischemia events (CIEs).…”
Section: Resultsmentioning
confidence: 99%
“…After screening of 5915 unique reports and assessing the full texts of 231 for eligibility, we included 73 studies reporting 28 625 patients with ≥50% ACAS (Figure 1; Table S2). 8–10,16–85…”
Section: Resultsmentioning
confidence: 99%
“…Some of these miRNAs differentially expressed in the circulation might be used as biomarkers of the progression of the diseases leading to ischemic stroke and their levels may help to identify patients with high risk of ischemic stroke who are eligible for carotid endarterectomy. Specifically, serum expression levels of miR-106b-5p [ 173 ], miR-92a [ 174 ], miR-19a-3p [ 175 ], miR-483-5p [ 176 ], miR-186-5p [ 177 ], miR-27b [ 178 ], and miR-342-5p [ 179 ] were found to be upregulated in asymptomatic ICAS patients versus controls, showing relatively high sensitivity and specificity in differentiating them from healthy subjects. Additionally, logistic regression analyses revealed an association between these miRNAs and the patients’ degree of carotid stenosis, as well as other vascular risk factors, such as diabetes, hypertension, and dyslipidemia.…”
Section: Mirnas As Regulators Of Atherosclerosis and Ischemic Strokementioning
confidence: 99%